Harnessing the power of simulation for assessment: Consensus recommendations for the use of simulation-based assessment in emergency medicine. Issue 2 (March 2020) - Hall, Andrew K.; Chaplin, Timothy; McColl, Tamara; Petrosoniak, Andrew; Caners, Kyla; Rocca, Nicole; Gardner, Carlyn; Bhanji, Farhan; Woods, Rob
ABSTRACT: Objectives: To address the increasing demand for the use of simulation for assessment, our objective was to review the literature pertaining to simulation-based assessment and develop a set of consensus-based expert-informed recommendations on the use of simulation-based assessment as presented at the 2019 Canadian Association of Emergency Physicians (CAEP) Academic Symposium on Education. Methods: A panel of Emergency Medicine (EM) physicians from across Canada, with leadership roles in simulation and/or assessment, was formed to develop the recommendations. An initial scoping literature review was conducted to extract principles of simulation-based assessment. These principles were refined via thematic analysis, and then used to derive a set of recommendations for the use of simulation-based assessment, organized by the Consensus Framework for Good Assessment. This was reviewed and revised via a national stakeholder survey, and then the recommendations were presented and revised at the consensus conference to generate a final set of recommendations on the use of simulation-based assessment in EM. Conclusion: We developed a set of recommendations for simulation-based assessment, using consensus-based expert-informed methods, across the domains of validity, reproducibility, feasibility, educational and catalytic effects, acceptability, and programmatic assessment. While the precise role of simulation-based assessment will be a subject of continued debate, we propose that these recommendations be used to assist educators and program leaders as they incorporate simulation-based assessment into their programs of assessment.